Leaps in Technology: Advanced MR Imaging after Total Hip Arthroplasty - Khodarahmi, Iman; Nittka, Mathias; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2017)
The vast majority of the metal-related artifacts in magnetic resonance imaging (MRI) arise from B0 inhomogeneity. These artifacts include failed fat suppression, signal loss, signal pileup, and image distortions. Metal artifact reduction sequence MRI has been used to mitigate these artifacts via optimization of the scan parameters and exploiting new techniques such as fully phase-encoded imaging and multispectral imaging including multi-acquisition variable-resonance image combination and slice encoding for metal artifact correction. Applicability of MRI in the vicinity of metal implants has been revolutionized by these new techniques at the expense of longer acquisition times. To reach clinically viable scan times, these novel techniques have been successfully coupled with various acceleration paradigms such as parallel imaging and compressed sensing.
Keywords: metal imaging; hip arthroplasty; artifact reduction; MARS; MRI; SEMAC; MAVRIC; compressed sensing